Project Monitoring Reveals Schedule Delays And Budget Deviations During Ship Maintenance: Pemantauan Proyek Mengungkap Keterlambatan Jadwal Dan Deviasi Anggaran Selama Pemeliharaan Kapal - Wahyu Tri Mulyana; Hery Irwan (Academia Open, 2026)
General Background Maritime maintenance operations require efficient coordination plus resource administration to preserve operational timelines alongside allocated finances. Specific Background At PT DOK dan Perkapalan Batam, historical documentation indicates persistent scheduling disparities and financial discrepancies across fifteen vessel restoration tasks. Knowledge Gap Conventional control systems often separate physical progress from financial reporting, preventing the early detection of simultaneous time and cost overruns. Aims This research evaluates the temporal and financial performance of fifteen maritime tasks using the Earned Value Management framework. Results Quantitative analysis reveals that all evaluated activities suffered from time extensions and financial expansions, evidenced by negative Schedule Variance alongside Cost Variance values, with performance indices strictly below one. Novelty This study provides a precise empirical demonstration of how fragmented tracking directly causes compounded operational losses in free-trade zone dockyard operations. Implications Maritime industries must transition toward integrated tracking frameworks to proactively mitigate material procurement issues while managing additional technical workloads. Highlights Quantitative EVM assessments indicate continuous time overruns across fifteen evaluated vessel restoration activities. Financial evaluations confirm systemic cost expansions resulting from material procurement issues plus unexpected technical tasks. Integrated tracking frameworks facilitate early detection of resource discrepancies to support proactive mitigation strategies. Keywords Earned Value Management; Project Performance; Time Control; Cost Control; Maritime Operations